Burkholderia contaminans isolated from root of blueberry shrub produces occidiofungins and pyrrolnitrin useful to prevent postharvest decays of blueberry fruits caused by Botrytis cinerea - Ferreira, Flavia Vanina; Rivadeneira, Maria Fernanda; Bello, Fernando; Giudici, Vanesa Noelia; Musumeci, Matías Alejandro (Wiley, 2025)
BACKGROUND: Botrytis cinerea is a relevant fungal pathogen in the production of blueberries, which is managed mainly with fungicides. However, the intensive usage has led to the emergence of resistant strains. The use of microbial biocontrol agents is a sustainable strategy to overcome limitations associated with fungicides. The objectives of this work were to know the capability of the endophytic bacterium Burkholderia contaminans 128 to inhibit different phytopathogens in vitro and to prevent B. cinerea rot in blueberry fruits. RESULTS: Burkholderia contaminans 128 able to grow on filaments of Trichoderma citrinoviride was isolated from roots of blueberry shrub. The bacterial cell-free supernatant (Bc128 CFS) inhibited efficiently the mycelia growth and conidia germination of B. cinerea and other important pathogens affecting blueberry such as Alternaria sp., Colletotrichum gloeosporioides and Fusarium graminearum. HPLC–MS/MS analyses of Bc128 CFS confirmed production of occidiofungins and pyrrolnitrin, compounds with fungicide activity but different inhibition mechanisms. Qualitative and quantitative HPLC-MS/MS analyses determined the presence of indole-3-acetic acid in Bc128 CFS, a phytohormone involved in plant-growth promotion. Bc128 CFS inhibited completely the natural occurrence of conidia of Alternaria sp., Colletotrichum sp. and Pestalotiopsis sp. and reduced significantly the incidence of B. cinerea conidia in blueberry flowers. Bc128 CFS decreased the virulence of B. cinerea in blueberries approximately 90%. Bc128 CFS was more efficient to control B. cinerea in preventive than curative treatments and did not affect fruit quality. CONCLUSION: B. contaminans 128 provides direct and indirect antibiosis mechanisms useful to prevent rots in blueberries caused by B. cinerea.